Sinteza orodij za analizo človeške napake po metodi analize spoznavne zanesljivosti in napak ter analize drevesa odpovedi - Zupančič, Janja (Strojniški vestnik, 2002)
In this paper we have looked at the synthesis of tools used for human-error analysis (Cognitive Realibility and Error Analysis Method - CREAM) and technical error or device error (fault tree) in such a way that a comparison between the results is possible. The synthesis was performed for an existing rectification system (column). Possible improvements are shown and suggested.
Keywords: metode CREAM; verjetnost napak; verjetnost okvar; drevo odpovedi; napake; odpoved; tehnološki procesi; rektifikacija